CONSIDERATION IN GENERAL ANESTHESIA TOWARDS PATIENT WITH SCHIZOPHRENIA TREATMENT: A CASE REPORT OF PSYCHIATRY-ANESTHESIOLOGY APPROACH - Yesyurun Sekundus Torrys; Dinar Kusuma Wardani; Charles Charles; Ida Bagus Krisna Jaya Sutawan; Ida Aju Kusuma Wardani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Anesthetic management in patients with schizophrenia receiving long-term antipsychotic therapy presents a clinical challenge due to the risk of drug interactions and perioperative complications, including hypotension, arrhythmias, and postoperative delirium. This study aimed to describe perioperative anesthetic management in a schizophrenic patient undergoing elective surgery. The study used a case report approach involving a 43-year-old female patient with left breast cancer and a history of undifferentiated schizophrenia treated with long-term fluphenazine and trifluoperazine therapy. Management included preoperative evaluation, intraoperative anesthesia planning, and postoperative monitoring. The patient underwent general anesthesia using propofol, fentanyl, and atracurium with close hemodynamic monitoring. The results showed that laboratory tests, ECG, and echocardiography were within normal limits, although intraoperative hypotension during induction and mild tachycardia during surgery were observed and successfully controlled without serious complications. Postoperative findings included mild agitation, postural hypotension, and shivering without delirium or severe cardiovascular disturbances. These findings indicate that comprehensive perioperative evaluation and individualized anesthetic strategies are essential to maintain patient stability and ensure surgical safety in schizophrenic patients receiving long-term antipsychotic therapy. ABSTRAK Manajemen anestesi pada pasien skizofrenia dengan terapi antipsikotik jangka panjang menjadi tantangan klinis karena risiko interaksi obat dan komplikasi perioperatif, seperti hipotensi, aritmia, dan delirium pascaoperasi. Penelitian ini bertujuan mendeskripsikan tata laksana anestesi perioperatif pada pasien skizofrenia yang menjalani operasi elektif. Metode yang digunakan berupa laporan kasus pada pasien perempuan usia 43 tahun dengan kanker payudara kiri dan riwayat skizofrenia undifferentiated yang mendapat terapi fluphenazine dan trifluoperazine jangka panjang. Penatalaksanaan meliputi evaluasi praoperatif, anestesi intraoperatif, dan pemantauan pascaoperatif. Pasien menjalani anestesi umum menggunakan propofol, fentanyl, dan atracurium dengan pemantauan hemodinamik ketat. Hasil menunjukkan pemeriksaan laboratorium, EKG, dan ekokardiografi dalam batas normal, dengan komplikasi intraoperatif berupa hipotensi saat induksi dan takikardia ringan yang dapat dikendalikan tanpa komplikasi serius. Pascaoperasi ditemukan agitasi ringan, hipotensi postural, dan menggigil tanpa delirium maupun gangguan kardiovaskular berat. Temuan ini menunjukkan bahwa evaluasi perioperatif yang komprehensif dan strategi anestesi terindividualisasi penting untuk menjaga stabilitas pasien skizofrenia selama tindakan pembedahan.